(untitled) (Journal of Hama University, 2026)
The research aims to test the impact of financial indicators on the trading volume of shares of traditional and Islamic banks listed on the Damascus Stock Exchange, during the period extending from the first quarter of 2011 until the fourth quarter of 2022 based on quarterly data.To achieve the goal of the research, we relied on some financial indicators represented by (return on assets ratio, market value to book ratio, debt ratio, cash readiness ratio, and fixed assets turnover rate) as independent variables, and trading volume as a dependent variable, with a number of controlling variables (fluctuations in stock returns, bank size), and using the autoregression methodology for distributed periods (ARDL), after studying the stability of the variables. The study found a positive and significant effect (of the return on assets ratio, debt ratio, and bank size) on the volume of stock trading, and a negative significant effect of the market value to book ratio on the volume of stock trading in the long term. In the short term, there was a negative and significant effect of the ratio of market value to book value on the trading volume of shares of the studied banks. While no effect was observed on the cash readiness ratio and fixed asset turnover rate on the trading volume of the studied banks’ shares in the short and long terms.